Marketing Channels of Sangkuriang Catfish (Clarias gariepinus) Hatchery Business in Karang Tunggal Village, Tenggarong Seberang District - Elena, Margaretha; Haqiqiansyah, Gusti; Darmansyah, Oon (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
This study aims to determine the marketing channel pattern of Sangkuriang Fahtoni catfish hatchery in Karang Tunggal Village, Tenggarong Seberang District, Kutai Kartanega Regency. This research was carried out from July 2022 to January 2023 at the Sangkuriang Fahtoni Catfish Hatchery, Karang Tunggal Village, Tenggarong Seberang District, Kutai Kartanegara Regency. The sampling method in research applies case study techniques. A sample of 1 respondent with reference to the census method. The results showed that there are 2 institutions involved in marketing activities at the Sangkuriang Fahtoni catfish hatchery, namely producers (Fahtoni hatchery business), retailers, and consumers. Marketing funnel pattern, level zero and level one marketing channel pattern.